Influence of voltage oscillation pulse-off time in a doms on the properties of hard hydrogen-free DLC coatings for the automotive industry. - Guliyev, Asif (2019)
Dissertação de Mestrado Conjunto Europeu em Tribologia de Superficies e Interfaces apresentada à Faculdade de Ciências e Tecnologia